2022
DOI: 10.3390/agronomy12030627
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Essential Oils from Aromatic Plant Ocimum sp.; A Comparative Biochemical Profiling and In-Silico Analysis

Abstract: Medicinal and aromatic plants (MAPs) are a rich source of bioactive compounds that are immensely important due to their potential use in pharmacological and agricultural applications. Here, we have evaluated the antimicrobial activity of essential oils (EOs) from three different species of Ocimum: O. gratissimum (EO1), O. tenuiflorum (EO2), and O. sanctum (EO3). The EOs were screened for antibacterial activity against pathogenic strains of Escherichia coli, Enterobacter cloacae and methicillin-resistant Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
4
10
0
Order By: Relevance
“…Therefore, antibiotic agents compete with p-amino benzoic acid to bind with the dihydropteroate synthetase (PDB ID: 2VEG) with much greater affinity and inhibit the formation of dihydrofolic acid. In line with the affinity showed by β-cubebene towards 2VEG (−6.1 kcal/mol) reported by Salvi et al [ 48 ], the sesquiterpenes in the current study—α-humulene and viridoflorol—showed similar affinity ( Table 5 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, antibiotic agents compete with p-amino benzoic acid to bind with the dihydropteroate synthetase (PDB ID: 2VEG) with much greater affinity and inhibit the formation of dihydrofolic acid. In line with the affinity showed by β-cubebene towards 2VEG (−6.1 kcal/mol) reported by Salvi et al [ 48 ], the sesquiterpenes in the current study—α-humulene and viridoflorol—showed similar affinity ( Table 5 ).…”
Section: Resultssupporting
confidence: 92%
“…Antibiotics bind to 3SRW and inhibit thymidine synthesis, which eventually affects DNA synthesis. In agreement with Jianu et al [ 49 ] and Salvi et al [ 48 ], sesquiterpenes exhibited higher in silico binding affinity towards 3SRW than well-known antibiotics used against enzymes such as trimethoprim. Viridiflorol had the highest binding energy (−8.1 kcal/mol) among all the examined volatiles towards all receptors included in the study.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These discs were transferred to MHA plates containing the test organism then were incubated at 37 °C for 24 h. After incubation, the diameter of the inhibition zone was measured and if it was found to be increased by ≥5 mm for either antibiotic combined with clavulanic acid, this was considered as evidence for the production of an ESBL (Schwaber et al. 2004 ; Jain and Mondal 2008 ).…”
Section: Methodsmentioning
confidence: 99%